A person-centered perspective on differential efficacy of early behavioral intervention in children with autism: A latent profile analysis. (September 2022) - Préfontaine, Isabelle; Morizot, Julien; Lanovaz, Marc J.; Rivard, Mélina
Abstract: Background: Individuals with autism spectrum disorder (ASD) present heterogeneous symptom manifestations and responses to intervention. Despite being well-established, early intensive behavioral intervention (EIBI) has produced inconsistent responding across studies. Investigating individual differences and identifying more homogenous subgroups in samples may lead to a better understanding of symptom heterogeneity in ASD and response to EIBI. Method: Adopting a person-centered perspective, we conducted latent profile analyses (LPA) to explore the presence of homogenous subgroups in our sample of 233 preschoolers with ASD receiving early behavioral intervention services. We investigated predictors of group membership using logistic multinomial regressions and outcomes of membership with the BCH approach available in Mplus. Results: We found four latent profiles in our sample: a mild impairment profile, a severe impairment profile, and two intermediate profiles with combinations of mild to moderate autistic symptoms, adaptive functioning, and intellectual functioning. Only the annual family income predicted profile membership. All profiles made progress during the intervention period, with varying magnitudes of change. During the follow-up period, the moderate impairment and the severe impairment profiles showed stability or improvement in adaptive functioning, while the two mild impairment profiles showed a slight decrease. Conclusions: Our study contributes to the literature by suggesting the presence of distinct profiles with differences in their response to EIBI. The profiles associated with better short-term outcomes were different than the profiles who maintain their gains more consistently over time. This finding may guide both practitioners and researchers assessing the effects of intervention. Highlights: Latent profile analysis identified four subgroups in preschoolers with autism. Profile membership was associated with differential response to intervention. Profile membership was associated with varying maintenance of gains. Finding may guide assessment the effects of intervention in research and practice.